The theoretical model of interaction between the baroclinic boundary layers of atmosphere and ocean - Ly, Le Ngoc (Vietnam Journal of Mechanics, 1980)
Presenting the theoretical model of the atmospheric and oceanic baroclinic boundary layers by interaction. Baroclinic effects of two boundary layers are described by the horizontal gradients of air temperature and water density in the equations of motion. The formulas computing the characteristics of the oceanic atmospheric baroclinic boundary layers were obtained. The above 1heoretical model is the general case of the model interaction of barotropic boundary layers.